Marching towards aesthetic security - Dutt, Som (Indian Horticulture, 2019)
The National Symposium on Recent Advances on Floriculture and Urban Horticulture in Global Perspective (NASRAFUH’18) was held during 4-5 January 2018 at Farmers’ Academy and Convention Centre, Kalyani, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, to address the novelty and importance of floriculture and urban horticulture in India in relevance to doubling of farmer’s income and exploring the business with floriculture. While inaugurating, Dr Dharani Dhar Patra, Vice-Chancellor, BCKV, Kalyani, stressed about the economic importance of ornamentals, diversification in floriculture, position and contribution of West Bengal regarding flower production, role of university serving as backfoot to provide research assistance in all aspects of floriculture, employment opportunities in floriculture for rural youth and women and also discussed the need of urban horticulture for wellbeing of urban populations. Dr Chirantan Chattopadhyay and Dr T. Janakiram, ADG (Hort. Sci.), ICAR, New Delhi, also described floricultural crops as best suited ones for doubling farmer’s income, providing aesthetic security.